Female-specific associations of serum perfluoroalkyl and polyfluoroalkyl substances with sex hormonal/insulin dysregulation: An integrated population-based study - Le-Xin Yang; Junyu Zhai; Zi-Jiang Chen; Yanzhi Du (Ecotoxicology and Environmental Safety)
Background: Ubiquitous perfluoroalkyl/polyfluoroalkyl substances (PFASs) exhibit sex-differential blood accumulation. However, sex- and age-specific links between PFASs and insulin-hormone dysregulation remain unknown. Methods: This population-based study utilized survey-weighted data from the National Health and Nutrition Examination Survey 2013–2016. Correlations between PFASs and sex hormone- or insulin-related indicators were assessed using a survey-weighted generalized linear model (SWGLM) for individual analyses and weighted quantile sum (WQS) regression for mixture analyses, stratified by sex and age. The mixture-related findings were validated with Bayesian kernel machine regression (BKMR) and further examined through stratification by menopausal status. Moreover, we investigated whether homeostatic model assessment of insulin resistance (HOMA-IR) mediated the relationships between sex hormones and monomethyl branched isomers of perfluorooctane sulfonate (Sm-PFOS) sex-specifically. Results: The following results persisted only in females. In SWGLM, linear perfluorooctanoate (n-PFOA) and homeostatic model assessment of β cell function (HOMA-β) were positively correlated in females, with this correlation strengthening in those aged ≥ 60. In WQS, PFAS mixture was positively associated with total testosterone/estradiol (TT/E2) and negatively associated with estradiol (E2) in females, but not in postmenopausal participants; the BKMR demonstrated trends consistent with prior findings. These associations intensified in females aged 20–59, with n-PFOA and perfluorohexane sulfonic acid (PFHxS) being main pollutants in the 20–39 and 40–59 age groups, respectively in WQS. The relationships between Sm-PFOS and both free androgen index and sex hormone-binding globulin (SHBG) were mediated by HOMA-IR. Conclusions: This cross-sectional study reveals female-specific associations between PFASs and insulin-hormone imbalance, suggesting multifaceted influences of PFASs on female endocrinology.